2022
DOI: 10.3390/su142315905
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Construction Applications and Life Cycle Sustainability of Natural Fiber Biocomposites

Abstract: The construction industry is continuously searching for sustainable materials to combat the rapid depletion of global resources and ongoing ecological crises. Biocomposites have recently received global attention in various industries due to their renewability, low cost, and biodegradability. Biocomposites’ potential as a sustainable substitute in construction can be understood by identifying their diverse applications. Moreover, examining their life cycle environmental and economic impacts is important. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Recently, scholars have researched the refinement of bio-based building materials, including straw bales [62]. Based on the research, quick-growing bio-materials show greater potential as carbon sinks due to their shorter rotation period, offering a greater capacity for carbon sequestration (Figure 5) [63]. Crop cycles of wheat and rice span less than a year, making them promising bio-based building materials.…”
Section: Reducing Carbon Emissionsmentioning
confidence: 99%
“…Recently, scholars have researched the refinement of bio-based building materials, including straw bales [62]. Based on the research, quick-growing bio-materials show greater potential as carbon sinks due to their shorter rotation period, offering a greater capacity for carbon sequestration (Figure 5) [63]. Crop cycles of wheat and rice span less than a year, making them promising bio-based building materials.…”
Section: Reducing Carbon Emissionsmentioning
confidence: 99%
“…Similarly, Gupta et al [151] introduced green tags that be assigned to explicit materials by taking into account various factors such as the route towards the end of the material's life cycle and green manufacturing. Likewise, Ahmad et al [152] analyzed life cycle assessment with natural fibre and synthetic fibre and found that biofibre saves 55% energy when compared with synthetic materials. As a result, plantbased bio-fibre processing has an environmental footprint that must be quantified, critical environmental aspects identified, and systems optimized so that overall impacts can be reduced, as well as the environmental impact of anticipated improvements in the supply chain and manufacturing processes.…”
Section: Crashworthiness Performance Of Natural Fibrementioning
confidence: 99%
“…In this way, biocomposites serve these purposes, as they present attractive characteristics such as: biodegradability, reduced costs, and wide availability and/or lower energy demand in their production, making them capable of competing with traditional materials existing in the current market. This type of materials can find application in various sectors, such as automotive, marine, aerospace, structural applications, infrastructure, packaging, and electronics [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%